2021
DOI: 10.26877/allure.v1i1.9213
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Expressive Speech Acts Used in Ellen Show " Interview with Billie Eilish"

Abstract: This research aims to identify types of expressive speech acts, to describe the realization and the actual condition used in Billie Eilish interview's in Ellen show. The researcher used descriptive qualitative. The data of this study collected from the interview script. In this research, the data are taken from the dialogue among the Interviewer and Interviewee; this research used document analysis for analyzing the data. The finding showed there were 16 utterances of expressive speech acts, which consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The researchers utilized a descriptive qualitative methodology for this study. As per Miles et al, (2014) In collecting the data, the method is observation, and the technique is note-taking. There were some steps for collecting the data.…”
Section: Methodsmentioning
confidence: 99%
“…The researchers utilized a descriptive qualitative methodology for this study. As per Miles et al, (2014) In collecting the data, the method is observation, and the technique is note-taking. There were some steps for collecting the data.…”
Section: Methodsmentioning
confidence: 99%
“…The strategies of speech act determine the success of how a speaker influences a hearer. In this case, there are two ways delivered, namely direct speech act and indirect speech act (Bonvillain, 2020;Ngasini, Senowarsito, & Muhrahani, 2021;Supri, I. Z., & Rahmatiany, n.d.;The Ellen Show, 2018).…”
Section: Expressive Speech Actmentioning
confidence: 99%
“…This talk show presents serious topics, comedies, and combination aspects such as music, game, human interest issues, to amuse audiences. Previous researchers studied expressive speech acts in Ellen talk show with famous and inspiring people like Billie Eillish (Ngasini, Senowarsito, & Muhrahani, 2021), Oprah Winfrey, Jennifer Aniston, Portia De Rossie (Saraswati, S. C., Sumani, & Chasanatun, 2022). Previous studies showed expressive language of speech act without explaining language functions as conversational strategy.…”
Section: Introductionmentioning
confidence: 99%
“…The speaker expresses sorrow or wrong doing for anything unpleasant by apologizing. (Ngasini, 2021) "I know. I am so sorry."…”
Section: Apologizingmentioning
confidence: 99%